E-learning and the science of instruction proven guidelines for consumers and designers of multimedia learning - Clark, Ruth Colvin (Pfeiffer essential resources for training and HR professionals., 2011)
"Thoroughly revised and updated, this third edition of the best-selling book offers a comprehensive review of multimedia learning for both users and designers. The book contains design principles that are written to increase learning while debunking many popular theories about good design. The book also contains the most current research and includes new topics (e-learning for educators, new delivery technologies, social media, and more) and offers helpful guidelines. The book's many examples: create working multimedia that inform the research guidelines; have been update to include real-world screen captures; extend principles to illustrate their application to synchronous e-learning tools"--